A Study of Photocopying Practice and Copyright Law in Nigeria Libraries: Librarians Perspectives - Saliu, Sambo, Atanda; Orewa, AHUTU, Avosuahi; Rabiu, Nafisat (American Journal of Social Sciences and Humanities, 2016)
Purpose: The study examine photocopying practice and copyright law in Nigeria libraries. Design/Methodology/Approach: A social survey method of research was adopted for the study. Five objectives and five research questions were formulated to guide the study. A systematic random sampling technique was used to select one hundred and fifty seven (157) respondents for the study whereas 91% were retrieved. The data collected were analyses using descriptive statistical tools such as, bar chart, percentages and mean. Findings: The outcome of the study revealed that libraries needs to play a prominent role in the issue of copyright law. The results also discovered that no limit to photocopied being made from textbooks and other libraries materials, more so, user’s awareness of copyright law does not influence their photocopying practice. Implication: The paper further emphasized that there should be adequate awareness of librarians in the issues of copyright law for effective and efficiency services delivery. Originality/Value: The paper value can be situated in its appropriate recommendations that libraries should derive a better means of effecting copyright law in Nigeria libraries and Ethics should be applied in the use of copyrighted library materials. Furthermore, law about ’fair use’ should not be abused in term of photocopying materials in the library and copyright law offenders should face criminal charges among others.